(untitled) (Journal of the College of Basic Education, 2022)
In recent decades, repercussions and calls have emerged for the need to reconsider the traditional methodology in education, which relies on indoctrination and stuffing information without thinking or contemplating. It called for new visions calling for the inevitability of adopting the systemic approach, as one of the methods of organizing content, which presents different experiences in a logical form, showing and confirming the interdependence, interaction, overlap, intertwining and integration between these experiences, and works to link and interact with the learner’s previous knowledge in his knowledge structure with what he will learn from New experiences, which makes what he learns meaningful and reduces the effort he exerts to link the new experiences with those he previously obtained, so that he can bring about a change in the form of the new knowledge gained and organize the information in an organized and networked manner.